The Effect of LLS Instruction on the Use of Writing Strategies in English by Foreign Postgraduate Students in India - Alshaghel, Mona; Pappuswamy, Dr. Umarani (International Journal of Language and Literary Studies, 2021)
This study intends to examine the impact of Strategy-Based Instruction on the strategy use by foreign post-graduate students, studying at two universities in India while writing in English. A total of one hundred students, who are non-native speakers of English, participated in this study. Fifty students in the experimental group received writing instruction through an online platform. The results were compared to their fifty counterparts in the control group. All the participants received an adapted version of the Strategy Inventory for Language Learning (SIIL) Questionnaire and a Writing Questionnaire as the pretest and posttest. Descriptive statistics and independent sample t-tests were run to analyze the data using SPSS. The findings showed that students who received language learning strategy instruction recorded higher scores than the students who did not receive any kind of instruction towards the skill of writing academic essays. The results revealed that students’ use of strategies in writing increased noticeably after strategy instruction and implied that students can be trained to use language-learning strategies successfully in their writing through direct strategy instruction.